2023
DOI: 10.3390/app131910896
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Peak Ground Acceleration and Seismogenic Fault Characteristics of the Mw7.8 Earthquake in Turkey

Yushi Duan,
Jingshan Bo,
Da Peng
et al.

Abstract: A Mw7.8 earthquake struck Turkey on 6 February 2023, causing severe casualties and economic losses. This paper investigates the characteristics of strong ground motion and seismogenic fault of the earthquake. We collected and processed the strong ground motion records of 379 stations using Matlab, SeismoSignal, and Surfer software: Matlab (Version R2016a), SeismoSignal (Version 5.1.0), and Surfer (Version 23.0.15), and obtained the peak ground acceleration (PGA) contour map. We analyzed the near-fault effect, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The second group of studies is dedicated to analyzing the characteristics of ground motions recorded in the earthquake sequence. Duan et al (2023) investigated the peak ground acceleration (PGA) and the seismogenic fault characteristics of the Mw 7.8 event; they identified the near-fault effect, the fault locking segment effect as well as the trampoline effect. By comparing the acceleration response spectra from the mainshock ground motions with the design spectrum of the Turkish seismic code, Papazafeiropoulos and Plevris (2023) concluded that modification of the Turkish seismic code is required to prescribe much larger seismic demands in earthquake-prone areas.…”
Section: Introductionmentioning
confidence: 99%
“…The second group of studies is dedicated to analyzing the characteristics of ground motions recorded in the earthquake sequence. Duan et al (2023) investigated the peak ground acceleration (PGA) and the seismogenic fault characteristics of the Mw 7.8 event; they identified the near-fault effect, the fault locking segment effect as well as the trampoline effect. By comparing the acceleration response spectra from the mainshock ground motions with the design spectrum of the Turkish seismic code, Papazafeiropoulos and Plevris (2023) concluded that modification of the Turkish seismic code is required to prescribe much larger seismic demands in earthquake-prone areas.…”
Section: Introductionmentioning
confidence: 99%